PENGARUH PENGUNGKAPAN MANAJEMEN RISIKO, KEPEMILIKAN INSTITUSIONAL DAN SENSITIVITAS MAKROEKONOMI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PELAYARAN DI BURSA EFEK INDONESIA (BEI) - Arlan Wijaya, (2022)
This research is a quantitative research that aims to determine the effect of Risk Management Disclosure, Institutional Ownership and Macroeconomic Sensitivity on Financial Distress at shipping companies on the Indonesia Stock Exchange (IDX). The data used is panel data of shipping companies on the Indonesia Stock Exchange (IDX), for the period 2016 - 2020. The research was carried out in two stages, first testing the potential financial distress score of the sample with the Modified Altman Z-Score model. Second, testing the effect of risk management disclosure, Institutional Ownership and Macroeconomic Sensitivity on financial distress with Logistics Regression using the Eviews program and significance level of 5%. The results of the first stage of testing obtained that the potential score for the modified Altman model was an average of 44.12% of shipping companies on the IDX from 2016-2020, in the distress area zone. The second stage, namely the disclosure of Risk Management, Institutional Ownership, Macroeconomic Sensitivity, namely the sensitivity of exchange rates, inflation, interest rates and oil prices, simultaneously affect financial distress. Partially, risk management disclosure and interest rate sensitivity have a significant effect on financial distress, while Institutional Ownership, exchange rate sensitivity, inflation, and oil prices have no effect.